Implantación del sistema de contabilidad en la empresa Econdi S.A., de la ciudad de Machala, durante el mes de septiembre del 2014 - Quezada Naula, Gilbert Carlos (2015)
This research paper entitled: Accounting System Implantation in the company ECONDI SA, city of Machala, during the month of September 2014, aims to analyze the application of an accounting system allowing to keep records of activities economic for better control of operations that are generated for the optimal development of the company, ie by real, reliable and timely information to the Financial Statements. It also allows comply with the guidelines required by the National University of Loja and as a prelude to choose the Engineer Degree in Accounting and Auditing, CPA requirement. All objectives in relation to the preparation of the Plan and Manual analysis, the design of accounting records were met; procedures that began with the lifting of inventory, general journal, sales assistants constituting valid for the implantation of the accounting process instruments and presentation of the financial statements reflect it relevant information that enabled real economic and financial situation of the company. At the end of the research the main conclusions and recommendations are presented primarily those relating to follow an organized with the application of the accounting system for the activity performed by the company and to allow access to real information and at the time required ; comply with tax obligations timely that allow the company framed within the law and avoid costly fines and unnecessary